Evaluasi Kinerja Keuangan Dan Efisiensi Belanja Daerah Pemerintah Kota Binjai Ditinjau Dari Rasio Keuangan - Raihatunnisa Bangun; Miftha Rizkina; Galih Supraja (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
The purpose of this study is to evaluate the regional financial performance of the Binjai City Government using financial ratio analysis and to assess the level of regional expenditure efficiency. Specifically, this research seeks to answer the following questions: (1) How is the financial performance of the Binjai City Government as measured by the autonomy ratio, effectiveness ratio, efficiency ratio, growth ratio, and harmony ratio? (2) To what extent is the level of regional expenditure efficiency achieved by the Binjai City Government? A descriptive quantitative research design was adopted, in which data were collected through documentation and literature review techniques. Financial ratio analysis was employed as the primary analytical tool to address both research questions. The findings indicate that the financial performance of the Binjai City Government has yet to reach an optimal level. The autonomy ratio was classified as very low, reflecting a substantial dependency on central government transfer funds; the effectiveness ratio failed to meet its targets due to unrealistic revenue planning; the efficiency ratio was categorized as inefficient, given that expenditures consistently exceeded revenues; the growth ratio remained unstable; and the harmony ratio was imbalanced between operational and capital expenditure. Regarding regional expenditure efficiency, although an overall improvement was observed, a persistent gap between budgeted and realized expenditures suggests that regional expenditure management has not been fully optimized.